2018
DOI: 10.1016/j.brs.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiologic effects of transcutaneous auricular vagus nerve stimulation (taVNS) via electrical stimulation of the tragus: A concurrent taVNS/fMRI study and review

Abstract: Stimulation of the tragus activates the cerebral afferents of the vagal pathway and combined with our review of the literature suggest that taVNS is a promising form of VNS. Future taVNS/fMRI studies should systematically explore various parameters and alternative stimulation targets aimed to optimize this novel form of neuromodulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
265
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 271 publications
(274 citation statements)
references
References 54 publications
8
265
1
Order By: Relevance
“…The extant literature suggests that tragus stimulation directly modulates the vagus network via the ABVN. We and others have demonstrated that stimulation of the ABVN has a direct effect on the afferent projection of the vagus nerve [29], with similarities in blood oxygen level dependent (BOLD) signal to cervically implanted VNS [42,43]. These fMRI findings suggest one possible mechanistic hypothesis for the immediate, sustained decrease in HR: stimulation is entering the afferent vagus system toward the central nervous system, activating the parasympathetic efferent cholinergic pathway and targeting the viscera, including the heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extant literature suggests that tragus stimulation directly modulates the vagus network via the ABVN. We and others have demonstrated that stimulation of the ABVN has a direct effect on the afferent projection of the vagus nerve [29], with similarities in blood oxygen level dependent (BOLD) signal to cervically implanted VNS [42,43]. These fMRI findings suggest one possible mechanistic hypothesis for the immediate, sustained decrease in HR: stimulation is entering the afferent vagus system toward the central nervous system, activating the parasympathetic efferent cholinergic pathway and targeting the viscera, including the heart.…”
Section: Discussionmentioning
confidence: 99%
“…1d). The active condition was direct electrical stimulation delivered to the inner side of the left tragus (anode in the ear canal, cathode on the surface of the tragus) as based on a review of several prior studies exploring the tragus nerve anatomy [19,23], tragus-evoked potentials [2426], auricular acupuncture trials [27,28], and a concurrent taVNS/fMRI trial [29]. …”
Section: Methodsmentioning
confidence: 99%
“…Outcomes from cadaveric studies make it tempting to speculate that the EAM, and in particular the posterior aspect, is supplied by the ABVN; this would be reasonable as Arnold's cough reflex has been consistently evoked in clinical studies by touching the inferoposterior wall of the ear canal (Gupta et al 1986;Tekdemir et al 1998). Nevertheless, fMRI evidence (see below) does not suggest that the posterior wall of the ear canal is a suitable site for ABVN stimulation, and these studies generally accept the inner tragus (Dietrich et al 2008;Kraus et al 2013;Yakunina et al 2017;Badran et al 2018b) and cymba concha (Frangos et al 2015;Yakunina et al 2017;Wang et al 2018) as active sites for vagal modulation, as supported by the cadaveric study conducted by Peuker & Filler (2002).…”
Section: Cadaveric Studiesmentioning
confidence: 99%
“…The outcomes of fMRI studies presented in Table 2 demonstrate considerable heterogeneity in the brain regions secondarily activated by auricular tVNS, which may be a result of differences in sex distribution, frequencies of stimulation and locations of outer-ear stimulation: the inner wall of the tragus (Kraus et al 2007;Dietrich et al 2008;Kraus et al 2013;Yakunina et al 2017;Badran et al 2018b), the posterior aspect of the ear canal (Kraus et al 2013) and the cymba concha (Frangos et al 2015;Yakunina et al 2017;Wang et al 2018). Indeed, there is evidence that different sites on the external ear can activate vagal centres to different degrees (Yakunina et al 2017).…”
Section: Functional Magnetic Resonance Imaging (Fmri)mentioning
confidence: 99%
“…The heart rate change with onset of stimulation was so reproducible that we adjusted positioning of the electrodes when the heart rate decrease was not observed, to ensure target attainment after burping or repositioning the infant. Our early experience in these neonates suggests that heart rate changes may be used to monitor taVNS stimulation and ensures CNS target engagement in terms of earlobe position and contact, and the individual dose [9,10]. …”
Section: Hr Reduction With Tavnsmentioning
confidence: 99%